The catch-up growth at 2 years of newborns born less than 32 weeks of gestational age - Tânia Moreira; Eugénia Matos; Susana Rebelo Pacheco; Manuel Cunha (Hygeia Press di Corridori Marinella, 2020)
Introduction: Very low birth weight newborns have an increased risk of neonatal complications and long-term malnutrition. In this paper the authors try to evaluate the catch-up growth of infants born with less than 32 weeks of gestational age (GA) and the effect of breast milk during the neonatal period on the later nutritional status, reflected on the somatometry at the age of 2. Material and methods: This is a retrospective study with a population of newborns with GA less than 32 weeks or weighing less than 1,500 grams, admitted to a level III Neonatal Intensive Care Unit between 2009 and 2012. Patients are divided into two groups: group 1, children with follow-up at 2 years of age; group 2, follow-up drop-out. Statistical analysis was performed using SPSS®, p-values < 0.05 were considered statistically significant. Results: 262 newborns were included, 158 (60.3%) had a clinical follow-up at 2 years-old. We found statistically significant differences between the two groups, regarding lower GA and head circumference z-score at birth, as well as increased risk of infection in group 1; comorbidities were more frequent in group 2. Birth weight z-score is the only variable that positively affects weight z-score. Follow-up weight z-score is positively affected by weight z-score at birth and negatively affected by the extent of in-hospital exclusive enteral feeding. GA and age at onset of exclusive enteral feeding do not present significant correlation. Intraperiventricular haemorrhage is associated with lower head circumference z-score at follow-up; in contrast, larger head circumference z-score at discharge and weight z-score at follow-up are associated with larger head circumference at follow-up. Conclusion: This study highlights how a deficient nutritional status at discharge delays a growth recovery at the age of 2, emphasizing the influence of birth weight and breast milk on growth.